Geologic and biologic controls on the evolution of reefs - Kießling, Wolfgang (Annual Review of Ecology Evolution and Systematics, 2009)
The shallow, tropical reef environment differs from other marine environments in its more intense competition for space, more limited nutrient concentrations, proliferation of clonal animals, and greater habitat complexity. The evolutionary consequences of these ecologic peculiarities are still poorly understood, but they seem to cause greater turnover rates of reef taxa than nonreef taxa and an especially volatile record of reefs on geologic timescales. The boom and bust pattern of Phanerozoic reef construction is impossible to explain by linear responses to physicochemical changes. Threshold effects appear to be involved not only in reef crises but also in reef expansions. Long-term climate change seems to influence the biotic composition of reefs, but neither climate nor sea-level nor chemical changes in the oceans can elucidate the waxing and waning of reefs. Biological factors affecting spatial competition are thus probably more important than geologic controls on reef evolution. Copyright © 2009 by Annual Reviews. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.geolog
Keywords: Climate change; Corals; Habitat area; Macroevolutionary resilience; Mass extinctions; Nutrients; Photosymbiosis